Antireflection film and image display apparatus
By forming a multi-layer reflective layer and a hard-mounted layer on the transparent film substrate of the foldable display device, the problem of cracking in the reflective layer during folding and stretching is solved, and higher bending resistance and stable performance at low temperatures are achieved.
Patent Information
- Application Number
- JP2023151260
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
In foldable display devices, cracks are prone to occur during repeated folding and stretching of the reflective layer, especially under low temperature conditions, the pressure resistance of the reflective layer is insufficient.
On the transparent film substrate, a hard-mounted layer and a reflective layer are formed respectively. The reflective layer consists of a multi-layer film, including a high-refractive index layer and a low-refractive index layer, and an inorganic matrix layer is added to the surface of the reflective layer to improve adhesion strength.
By optimizing the structure and material of the reflective layer, the bending resistance of the reflective layer is significantly improved, the risk of cracks during folding and stretching is reduced, and good performance is maintained under low temperature conditions.
Smart Images

Figure 2025043779000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an antireflection film having an antireflection layer on a hard coat layer, and further to an image display device having the antireflection film. [Background technology]
[0002] Anti-reflection films are used on the viewing side surfaces of image display devices such as liquid crystal displays and organic EL displays for the purposes of preventing deterioration of image quality due to reflection of external light, improving contrast, etc. Anti-reflection films have an anti-reflection layer made of a laminate of multiple thin films with different refractive indices on a transparent film.
[0003] For example, Patent Document 1 discloses an antireflection film having a SiO primer layer on a hard coat film, and an antireflection layer thereon consisting of an alternating laminate of a niobium oxide (Nb2O5) layer as a high refractive index layer and a silicon oxide (SiO2) layer as a low refractive index layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-47876 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, a foldable image display device (foldable display) equipped with an organic EL panel using a foldable substrate (flexible substrate) such as a resin film has been put to practical use. For example, an anti-reflection film having an anti-reflection layer provided on a flexible substrate is used as a cover window of the foldable display.
[0006] In a foldable display, bending and stretching are repeated at the same location. In a bent state (folded state, closed state), compressive stress is applied to the inside of the bent location, and tensile stress is applied to the outside. When the display is folded with the display surface on the inside, the anti-reflection film is folded with the anti-reflection layer-forming surface on the inside. When folding a foldable display, an operation is performed from an extended state (open state) to a bent state (closed state), and a compressive stress is applied to the anti-reflection layer of the anti-reflection film. When opening a foldable display, an operation is performed from a bent state (closed state) to an extended state (open state), and the compressive stress of the anti-reflection layer is released.
[0007] When the foldable display is repeatedly opened and closed, the application and release of compressive stress to the anti-reflection layer of the anti-reflection film is repeated, which may cause cracks in the anti-reflection layer. Furthermore, when the foldable display is opened and closed after being kept at a low temperature, a larger stress change occurs, which makes the anti-reflection layer more likely to crack.
[0008] Antireflection films used in foldable displays are required to be less susceptible to cracking in the antireflection layer when repeatedly opened and closed, and also to be less susceptible to cracking when opened and closed at low temperatures.
[0009] In view of the above, an object of the present invention is to provide an antireflection film that is unlikely to develop cracks in the antireflection layer when a device is repeatedly opened and closed, and has excellent flex resistance. [Means for solving the problem]
[0010] The anti-reflection film comprises a hard coat layer and an anti-reflection layer in this order on one main surface of a transparent film substrate. The anti-reflection layer is made of a plurality of thin films having different refractive indices. Specifically, the anti-reflection layer comprises at least one high refractive index layer and at least one low refractive index layer. The anti-reflection layer may comprise two or more low refractive index layers and two or more high refractive index layers. The anti-reflection layer may comprise an inorganic primer layer on the surface in contact with the hard coat layer.
[0011] The anti-reflection film preferably has a reflectance of 1% or less.
[0012] When the anti-reflection film is bent 180° with the anti-reflection layer side facing inward at a bending radius of 2 mm, the maximum compressive stress S of the hard coat layer is measured. HC The compressive stress of the antireflection layer is 375 MPa or less, and the maximum compressive stress of the antireflection layer is 530 MPa or less. The compressive stress is a calculated value using a finite element model.
[0013] The high refractive index layer of the antireflection layer is preferably a thin film mainly composed of niobium oxide. When the high refractive index layer is a niobium oxide thin film, the ratio of the film thickness of the high refractive index layer to the total film thickness of the antireflection layer is preferably 10 to 40%. The low refractive index layer of the antireflection layer is preferably a thin film mainly composed of silicon oxide.
[0014] The indentation elastic modulus of the antireflection layer is preferably 20 to 24 GPa.
[0015] The thickness of the hard coat layer is preferably 1 to 10 μm, and the indentation modulus of the hard coat layer is preferably 6.5 to 11 GPa. Effect of the Invention
[0016] The anti-reflection film of the present invention has excellent bending resistance, and even if the anti-reflection layer is repeatedly bent and extended with the anti-reflection layer formed surface on the inside, cracks are unlikely to occur in the anti-reflection layer. Therefore, the anti-reflection film of the present invention can be suitably used for a foldable display. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a cross-sectional view showing a lamination configuration of an antireflection film according to an embodiment. [Diagram 2] FIG. 13 is a diagram showing a model of a bent state of an antireflection film used in finite element model calculations. [Diagram 3]FIG. 2 is a diagram showing the bending radius direction and the direction of compressive stress in a bent state of an antireflection film. [Figure 4] 1 is a graph plotting the thickness direction and stress values of an antireflection film in a bent state, which were obtained by finite element model calculation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] [Composition of anti-reflective film] 1 is a cross-sectional view showing an example of a laminated structure of an antireflection film according to one embodiment of the present invention. The antireflection film 100 has a hard coat layer 2 on one main surface of a transparent film substrate 1, and an antireflection layer 5 on the hard coat layer 2.
[0019] <Transparent film substrate> The visible light transmittance of the transparent film substrate 10 is preferably 80% or more, more preferably 90% or more. The resin material constituting the transparent film substrate 10 is preferably a resin material having excellent transparency, mechanical strength, and thermal stability. Specific examples of the resin material include cellulose-based resins such as triacetyl cellulose, polyester-based resins, polyethersulfone-based resins, polysulfone-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyolefin-based resins, (meth)acrylic-based resins, cyclic polyolefin-based resins (norbornene-based resins), polyarylate-based resins, polystyrene-based resins, polyvinyl alcohol-based resins, and mixtures thereof.
[0020] The thickness of the transparent film substrate is not particularly limited, but from the viewpoints of strength, workability such as handleability, thin layer property, etc., it is preferably about 5 to 300 μm, more preferably 10 to 250 μm, and even more preferably 20 to 200 μm.
[0021] <Hard coat layer> A hard coat film is formed by providing a hard coat layer 2 on the main surface of a transparent film substrate 1. The hard coat layer is a cured resin layer, and is formed by applying a composition containing a curable resin onto the transparent film substrate and curing the resin component.
[0022] As the curable resin (binder resin) of the hard coat layer 2, a curable resin such as a thermosetting resin, a photocurable resin, or an electron beam curable resin is preferably used. The types of the curable resin include polyester-based, acrylic-based, urethane-based, amide-based, silicone-based, silicate-based, epoxy-based, melamine-based, and oxetane-based resins. Among these, acrylic-based and epoxy-based resins are preferred because of their high hardness and the ability to be photocured, and acrylic resins are particularly preferred.
[0023] The photocurable hard coat material includes a polyfunctional compound having two or more photopolymerizable (preferably ultraviolet-polymerizable) functional groups. The polyfunctional compound may be a monomer or an oligomer. The acrylic hard coat material includes a compound (polyfunctional (meth)acrylate) containing two or more (meth)acryloyl groups in one molecule. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0024] Specific examples of polyfunctional compounds having two or more (meth)acryloyl groups in one molecule include bifunctional (meth)acrylates such as tricyclodecane dimethanol diacrylate, pentaerythritol di(meth)acrylate, 1,6-hexanediol (meth)acrylate, 1,9-nonanediol diacrylate, 1,10-decanediol (meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and dipropylene glycol diacrylate; and trifunctional or higher (meth)acrylates such as pentaerythritol tri(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol tetra(meth)acrylate, dimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid tri(meth)acrylate, ethoxylated glycerin triacrylate, and ethoxylated pentaerythritol tetraacrylate.
[0025] The polyfunctional (meth)acrylate may be a urethane (meth)acrylate. The urethane (meth)acrylate may be a urethane di(meth)acrylate having two (meth)acryloyl groups, or may be one having three or more (meth)acryloyl groups. From the viewpoint of the hardness of the hard coat layer, the number of (meth)acryloyl groups in the urethane (meth)acrylate is preferably 3 or more, more preferably 4 to 15, and even more preferably 6 to 12. In the case of a urethane (meth)acrylate oligomer, the molecular weight is, for example, 3000 or less, preferably 500 to 2500, and more preferably 800 to 2000.
[0026] The content of the polyfunctional compound in the hard coat material is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and even more preferably 70 parts by weight or more, based on 100 parts by weight of the total of resin components (monomers, oligomers, and prepolymers that form a binder resin by curing). If the content of the polyfunctional compound is within the above range, the hardness of the hard coat layer tends to be increased.
[0027] The hard coat material may contain a bifunctional polyfunctional compound and a trifunctional or higher polyfunctional compound as a polyfunctional compound. For example, an acrylic hard coat material may contain a bifunctional polyfunctional (meth)acrylate and a trifunctional or higher polyfunctional (meth)acrylate. The higher the ratio of the trifunctional or higher polyfunctional compound contained in the hard coat material, the higher the hardness of the hard coat layer and the larger the indentation elastic modulus of the hard coat layer.
[0028] The hard coat material may contain fine particles in addition to the binder resin, which allows the hardness, surface shape, refractive index, etc. of the hard coat layer to be adjusted.
[0029] As the fine particles, inorganic oxide fine particles such as silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide, glass fine particles, and crosslinked or uncrosslinked organic fine particles made of transparent polymers such as polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate can be used without any particular limitation.
[0030] The average particle size (average primary particle size) of the fine particles is preferably about 10 nm to 10 μm. The average primary particle size is the weight average particle size measured by the Coulter count method. Depending on the particle size, the fine particles can be roughly divided into fine particles having a particle size of about 0.5 μm to 10 μm, submicron or μm order (hereinafter sometimes referred to as "microparticles"), fine particles having a particle size of about 10 nm to 100 nm (hereinafter sometimes referred to as "nanoparticles"), and fine particles having a particle size intermediate between microparticles and nanoparticles.
[0031] By including nanoparticles in the hard coat layer 2, fine irregularities are formed on the surface, and the adhesion between the hard coat layer 2 and the antireflection layer 5 tends to be improved. As the nanoparticles, inorganic fine particles are preferable, and inorganic oxide fine particles are more preferable. Among them, silica particles are preferable because they have a low refractive index and can reduce the difference in refractive index with the binder resin.
[0032] The hard coat material contains the above-mentioned binder resin component, and if necessary, contains a solvent capable of dissolving the binder resin component. As described above, the hard coat material may contain fine particles. When the binder resin component is a photocurable resin, it is preferable that a photopolymerization initiator is contained in the composition. In addition to the above, the hard coat material may contain additives such as a leveling agent, a thixotropic agent, an antistatic agent, an antiblocking agent, a dispersant, a dispersion stabilizer, an antioxidant, an ultraviolet absorber, an antifoaming agent, a thickener, a surfactant, and a lubricant.
[0033] A hard coat layer is formed by applying a hard coat material onto a transparent film substrate, and removing the solvent and curing the resin as necessary. Any suitable method such as bar coating, roll coating, gravure coating, rod coating, slot orifice coating, curtain coating, fountain coating, and comma coating may be adopted as a method for applying the hard coat material. The heating temperature after application may be set to an appropriate temperature depending on the composition of the hard coat material, and is, for example, about 50°C to 150°C. When the binder resin component is a photocurable resin, photocuring is performed by irradiating it with active energy rays such as ultraviolet rays. The integrated light amount of the irradiated light is preferably 100 to 500 mJ / cm. 2 That's about it.
[0034] Before forming the antireflection layer 5 on the hard coat layer 2, the hard coat layer 2 may be subjected to a surface treatment. Examples of the surface treatment include surface modification treatments such as corona treatment, plasma treatment, flame treatment, ozone treatment, glow treatment, alkali treatment, acid treatment, and treatment with a coupling agent. By subjecting the hard coat layer 2 to a surface treatment, it is expected that the surface shape can be adjusted and the adhesion to the antireflection layer 5 can be improved.
[0035] The thickness of the hard coat layer 2 is not particularly limited, but from the viewpoint of achieving both high hardness and flex resistance, it is preferably 1 to 10 μm, more preferably 2 to 9 μm, and even more preferably 3 to 8 μm. If the thickness of the hard coat layer is too large, the flex resistance tends to be insufficient. If the thickness of the hard coat layer is too small, the hardness tends to be insufficient.
[0036] The indentation elastic modulus of the hard coat layer is preferably 6.5 to 11 GPa, more preferably 7 to 10.5 GPa, and may be 7.5 to 10 GPa. The indentation elastic modulus of the hard coat layer is determined from the slope of the unloading curve at a depth of about 300 nm when an indentation test is performed by pressing the indenter of a nanoindenter into the hard coat layer portion of the cross section of the antireflection film.
[0037] When the indentation modulus of the hard coat layer is excessively large, the compressive stress of the hard coat layer increases when the antireflection film is bent, and the bending resistance tends to be insufficient. On the other hand, when the indentation modulus of the hard coat layer is excessively small, the compressive stress of the hard coat layer increases when the antireflection film is bent, and the bending resistance tends to be insufficient.
[0038] By selecting the hard coat material, the indentation modulus of the hard coat layer can be adjusted to a desired range. As mentioned above, the higher the ratio of the multifunctional compound having three or more functional groups contained in the hard coat material, the higher the indentation modulus of the hard coat layer tends to be. In addition, when the hard coat layer contains inorganic oxide particles such as silica, the indentation modulus tends to be higher.
[0039] <Anti-reflection layer> The antireflection layer 5 is a multilayer film made of multiple thin films with different refractive indices, including at least one high refractive index layer and at least one low refractive index layer. In general, the optical thickness (product of refractive index and film thickness) of the thin films of the antireflection layer is adjusted so that the inverted phases of the incident light and the reflected light cancel each other out. A multilayer stack of multiple thin films with different refractive indices can reduce the reflectance in a wide wavelength range of visible light.
[0040] Examples of materials for the thin film constituting the antireflection layer 5 include inorganic materials such as metal oxides, nitrides, and fluorides. The antireflection layer 5 is preferably an alternating laminate of high refractive index layers and low refractive index layers. In order to reduce reflection at the air interface, the thin film 54 provided as the outermost layer (the layer farthest from the hard coat layer 2) of the antireflection layer 5 is preferably a low refractive index layer.
[0041] The high refractive index layers 51 and 53 have a refractive index of, for example, 1.9 or more, preferably 2.0 or more. Examples of high refractive index materials include titanium oxide, niobium oxide, zirconium oxide, tantalum oxide, zinc oxide, indium oxide, indium tin oxide (ITO), and antimony-doped tin oxide (ATO). Among them, the high refractive index layers 51 and 53 are preferably thin films mainly composed of niobium oxide, since they have a high refractive index and can efficiently reduce reflected light by laminating with a low refractive index layer. The high refractive index layers may contain metal oxides other than niobium oxide, but the content of niobium oxide is preferably 90% by weight or more, more preferably 99% by weight or more.
[0042] The low refractive index layers 52, 54 have a refractive index of 1.6 or less, preferably 1.5 or less. Examples of low refractive index materials include silicon oxide, titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, and lanthanum fluoride. Among them, the low refractive index layers 52, 54 are preferably thin films mainly composed of silicon oxide, since they have a low refractive index, high hardness, and can efficiently reduce the reflectance by laminating with a niobium oxide high refractive index layer. The low refractive index layers 52, 54 preferably have a silicon oxide content of 90% by weight or more, more preferably 99% by weight or more.
[0043] The thickness of each of the high refractive index layer and the low refractive index layer is about 5 to 200 nm, and preferably about 15 to 150 nm. The thickness of each layer may be designed according to the refractive index, the layer structure, etc., so that the reflectance of visible light is small.
[0044] In one embodiment, the antireflection layer 5 is an alternating laminate of four layers in total, including, from the hard coat layer 2 side, a first layer: a niobium oxide thin film as a high refractive index layer 51, a second layer: a silicon oxide thin film as a low refractive index layer 52, a third layer: a niobium oxide thin film as a high refractive index layer 53, and a fourth layer: a silicon oxide thin film as a low refractive index layer 54. In another embodiment, the antireflection layer is an alternating laminate of six layers in total, including three niobium oxide thin films as high refractive index layers and three silicon oxide thin films as low refractive index layers.
[0045] When the antireflection layer 5 is an alternating laminate of a total of four layers consisting of two high refractive index layers 51, 53 and two low refractive index layers 52, 54, an example of a configuration having, from the hard coat layer 2 side, a niobium oxide thin film 51 having a thickness of 10 to 20 nm, a silicon oxide thin film 52 having a thickness of 35 to 45 nm, a niobium oxide thin film 53 having a thickness of 25 to 35 nm, and a silicon oxide thin film 54 having a thickness of 90 to 105 nm, in that order.
[0046] When the high refractive index layer of the antireflection layer 5 is a niobium oxide thin film, the ratio of the film thickness of the high refractive index layer (niobium oxide thin film) to the total film thickness of the antireflection layer is preferably 10 to 40%, more preferably 15 to 30%. Niobium oxide has a high density, so the larger the film thickness ratio of the niobium oxide thin film in the antireflection layer, the larger the indentation elastic modulus of the antireflection layer tends to be. When the film thickness ratio of the niobium oxide thin film is excessively large, the indentation elastic modulus of the antireflection layer is large, and the antireflection film tends to have poor bending resistance. On the other hand, when the film thickness ratio of the niobium oxide thin film is excessively small, it is difficult to achieve an appropriate optical design for reducing the reflectance, so the reflectance (reflection Y value) of the antireflection film tends to be large.
[0047] From the viewpoint of enabling optical design that reduces the indentation elastic modulus of the antireflection layer and reduces the reflectance of the antireflection film by setting the film thickness ratio of niobium oxide within the above range, the total film thickness of the antireflection layer is preferably 160 to 230 nm, and may be 170 to 220 nm or 180 to 210 nm.
[0048] The indentation elastic modulus of the antireflection layer is preferably 20 to 24 GPa, more preferably 21 to 23 GPa. The indentation elastic modulus of the antireflection layer is determined from the slope of the unloading curve at a depth of about 10 nm when an indentation test is performed by laminating an antireflection film on a glass plate and indenting the surface of the antireflection layer with the indenter of a nanoindenter.
[0049] When the indentation modulus of the anti-reflection layer is too large, the compressive stress of the hard coat layer and the anti-reflection layer becomes large when the anti-reflection film is bent, and the bending resistance tends to be insufficient.On the other hand, when the indentation modulus of the anti-reflection layer is too small, the hardness of the anti-reflection film tends to be insufficient.
[0050] In an antireflection layer in which a niobium oxide thin film as a high refractive index layer and a silicon oxide thin film as a low refractive index layer are alternately laminated, a configuration in which the thickness of the niobium oxide thin film on the surface side of the antireflection layer is large is adopted as an optical design for reducing the reflectance. In such an optical design, the ratio of the thickness of the niobium oxide thin film to the total thickness of the antireflection layer exceeds 40%, so that the indentation modulus of the antireflection layer is large and the flex resistance may be poor. By reducing the thickness ratio of the niobium oxide thin film and reducing the indentation modulus of the antireflection layer within a range where an appropriate optical design for reducing the reflectance is possible, an antireflection film with excellent flex resistance can be obtained.
[0051] The antireflection layer 5 may have an inorganic primer layer 50 on the surface in contact with the hard coat layer 2, and may have a high refractive index layer and a low refractive index layer thereon. By providing the inorganic primer layer 50 in contact with the hard coat layer 2, the adhesion between the hard coat layer 2 and the antireflection layer 5 tends to be improved.
[0052] Examples of materials for the inorganic primer layer 50 include metals such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, indium, tungsten, aluminum, zirconium, and palladium; alloys of these metals; and oxides, fluorides, sulfides, and nitrides of these metals. Among these, the material for the inorganic primer layer is preferably an inorganic oxide, and silicon oxide or indium oxide is particularly preferred. The inorganic oxide constituting the inorganic primer layer 50 may be a composite oxide such as indium tin oxide (ITO).
[0053] The inorganic primer layer 50 has a thickness of, for example, about 0.5 to 15 nm, and preferably 1 to 10 nm. When the inorganic primer layer has a thickness in the above range, it is possible to achieve both adhesion to the hard coat layer 2 and high light transmittance. Since the inorganic primer layer 50 has a smaller thickness than the high refractive index layers 51, 53 and the low refractive index layers 52, 54, the presence or absence of the inorganic primer layer does not have a significant effect on the indentation elastic modulus or flex resistance of the antireflection layer 5.
[0054] The method for forming the thin film constituting the antireflection layer 5 is not particularly limited, and may be either a wet coating method or a dry coating method. Dry coating methods such as vacuum deposition, CVD, sputtering, and electron beam vapor deposition are preferred because they can form a thin film with a uniform thickness. Among them, sputtering is preferred because it has excellent uniformity in thickness and is easy to form a dense film.
[0055] In the sputtering method, a thin film can be continuously formed while a long hard coat film is transported in one direction (longitudinal direction) by a roll-to-roll method, so that the productivity of the antireflection film can be improved. In order to improve the productivity of the antireflection film, it is preferable to form all the thin films constituting the antireflection layer 5 by the sputtering method.
[0056] In the sputtering method, the film is formed while introducing an inert gas such as argon, and if necessary, a reactive gas such as oxygen, into the chamber. The formation of the oxide layer by the sputtering method can be carried out by either a method using an oxide target or reactive sputtering using a metal target. In order to form a metal oxide film at a high rate, reactive sputtering using a metal target is preferred.
[0057] <Anti-stain layer> The antireflection film may have an antifouling layer (not shown) as an outermost layer (topcoat layer) on the antireflection layer 5. By providing the antifouling layer on the outermost surface, the influence of contamination from the external environment (fingerprints, hand dirt, dust, etc.) can be reduced and contaminants attached to the surface can be easily removed.
[0058] In order to maintain the antireflection properties of the antireflection layer 5, it is preferable that the antifouling layer 7 has a small difference in refractive index from the low refractive index layer 54 which is the outermost layer of the antireflection layer 5. The refractive index of the antifouling layer 7 is preferably 1.6 or less, more preferably 1.55 or less.
[0059] The material of the antifouling layer 7 is preferably a fluorine-containing compound. The fluorine-containing compound not only imparts antifouling properties but also contributes to lowering the refractive index. Among them, a fluorine-based polymer containing a perfluoropolyether skeleton is preferable because it has excellent water repellency and can exhibit high antifouling properties. From the viewpoint of enhancing antifouling properties, perfluoropolyether having a main chain structure that can be rigidly arranged in parallel is particularly preferable. As a structural unit of the main chain skeleton of perfluoropolyether, a perfluoroalkylene oxide having 1 to 4 carbon atoms that may have a branch is preferable, and examples thereof include perfluoromethylene oxide (-CF2O-), perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), and perfluoroisopropylene oxide (-CF(CF3)CF2O-).
[0060] The antifouling layer 7 can be formed by a wet process such as a reverse coating method, a die coating method, a gravure coating method, etc., or a dry process such as a vacuum deposition method, a CVD method, etc. The thickness of the antifouling layer is usually about 2 to 20 nm, and the larger the thickness of the antifouling layer 7, the more improved the antifouling properties tend to be.
[0061] When the antireflection film has an antifouling layer, the indentation elastic modulus when an indenter is pressed into the antireflection film from the surface of the antifouling layer is taken as the indentation elastic modulus of the antireflection layer. Since the antifouling layer is sufficiently thin compared to the antireflection layer, even if the antifouling layer is present, the influence on the measurement of the indentation elastic modulus of the antireflection layer is slight.
[0062] [Compressive stress in bending state] When the anti-reflection film is bent 180° with the anti-reflection layer side facing inward at a bending radius of 2 mm, the maximum compressive stress S of the hard coat layer is measured. HC is 375 MPa or less, and the maximum value of the compressive stress of the antireflection layer is 530 MPa or less.
[0063] The compressive stress in the bent state is a value calculated by a finite element model calculation in which the cross section of the antireflection film is divided into finite elements by a two-dimensional mesh. The method of the model calculation is as described in the Examples below.
[0064] When the anti-reflection film is bent with the anti-reflection layer side facing inward, as shown in Figure 4, a negative stress (compressive stress) is applied to the anti-reflection layer side, and the compressive stress (absolute value of stress) of the hard coat layer (HC) is maximum at the point where the thickness coordinate is maximum, i.e., at the interface with the anti-reflection layer (AR), and the compressive stress of the anti-reflection layer (AR) is maximum at the surface (the surface opposite the hard coat layer). Therefore, the maximum compressive stress S of the hard coat layer is HC is the compressive stress at the interface between the hard coat layer and the antireflection layer, and the maximum compressive stress S AR is the compressive stress at the surface of the antireflective layer.
[0065] Compressive stress S of the hard coat layerHC and the compressive stress S of the anti-reflection layer AR The smaller the value, the more excellent the bending resistance of the antireflection film, and the occurrence of cracks in the antireflection layer when opening and closing operations are repeated or when opening and closing operations are performed at low temperatures tends to be suppressed.
[0066] Compressive stress S of the hard coat layer HC The compressive stress S of the hard coat layer is preferably 370 MPa or less, more preferably 365 MPa or less, and even more preferably 360 MPa or less. HC may be 300 MPa or more, 330 MPa or more, 340 MPa or more, or 345 MPa or more.
[0067] Compressive stress S of the anti-reflection layer AR The compressive stress S of the antireflection layer is preferably 525 MPa or less, more preferably 520 MPa or less, even more preferably 515 MPa or less, and may be 510 MPa or less or 505 MPa or less. AR may be 450 MPa or more, 460 MPa or more, 470 MPa or more, or 480 MPa or more.
[0068] The smaller the indentation elastic modulus of the anti-reflection layer, the greater the compressive stress S AR and the compressive stress S of the hard coat layer HC The smaller the indentation modulus of the hard coat layer, the smaller the compressive stress S HC tends to be smaller, and the compressive stress S of the anti-reflection layer AR The thickness of the hard coat layer and the thickness of the anti-reflection layer do not have a significant effect on the compressive stress. However, when the thickness of the hard coat layer exceeds 10 μm, the compressive stress S of the hard coat layer tends to increase. HC increases rapidly and bending resistance tends to decrease.
[0069] By utilizing the above knowledge, it is possible to design an anti-reflection film with excellent bending resistance. That is, since the physical properties of the transparent film substrate, the hard coat layer, and the anti-reflection layer are known, a finite element model calculation is performed using each physical property, and the compressive stress S of the hard coat layer and the anti-reflection layer is calculated. HC and S AR By calculating S, it is possible to predict the bending resistance of the anti-reflection film. HC and S AR It is also possible to select the material and thickness of each layer so that the difference in the bending resistance between the anti-reflection film and the film is smaller. Therefore, by utilizing the findings of the present invention, it is possible to design an anti-reflection film having better bending resistance without repeatedly fabricating the anti-reflection film and carrying out a bending resistance test.
[0070] Although the antireflection layer is a multilayer film, it can be approximated as a bulk single layer in the model calculation. Specifically, if the thickness of the kth layer is d k , the indentation modulus is E k The anti-reflection layer with an n-layer structure has an indentation modulus of (Σd k E k ) / (Σd k ) As mentioned above, the primer layer is thinner than the antireflection layer, so the primer layer does not need to be taken into account in the model calculation.
[0071] [Usage of anti-reflective film] The anti-reflection film is used by being disposed on the surface of an image display device such as a liquid crystal display or an organic EL display. For example, by disposing the anti-reflection film on the viewing side surface of a panel including an image display medium such as a liquid crystal cell or an organic EL cell, the reflection of external light can be reduced and the visibility of the image display device can be improved. The reflectance (reflection Y value) of the anti-reflection film is preferably 1% or less, more preferably 0.5% or less.
[0072] The anti-reflection film of the present invention has excellent bending resistance, and even when the anti-reflection layer-forming surface is faced to the inside and subjected to repeated opening and closing operations (bending and stretching) or opening and closing operations are performed at low temperatures, cracks in the anti-reflection layer are unlikely to occur at the bending points, and therefore the film can also be suitably used for foldable displays. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following specific examples.
[0074] [Preparation of hard coat composition] <Hard Coat Composition A> 100 parts by weight of an ultraviolet-curable multifunctional acrylic resin composition ("Z-850-50H-D" manufactured by AICA Corporation, solid content concentration: 44% by weight), 4 parts by weight of a photopolymerization initiator ("Omnirad2959" manufactured by IGM Resins), and 0.05 parts by weight of a leveling agent ("LE-303" manufactured by Kyoeisha Chemical) were mixed and diluted with methyl isobutyl ketone to obtain a hard coat composition A with a solid content concentration of 40% by weight.
[0075] <Hard Coat Composition B> Hard coat composition B was prepared in the same manner as hard coat composition A, except that the ultraviolet-curable multifunctional acrylic resin composition was changed to AICA Kogyo's "Z-850-27H2AL" (solid content: 44% by weight).
[0076] <Hard Coat Composition C> Hard coat composition C was prepared in the same manner as hard coat composition A, except that the ultraviolet-curable polyfunctional acrylic resin composition was changed to "Lioduras LCH2478NLS7" manufactured by Toyochem.
[0077] <Hard Coat Composition D> Hard coat composition D was prepared by mixing the above hard coat composition B and hard coat composition C in a weight ratio of 1:3.
[0078] <Hard Coat Composition E> The above hard coat composition C and hard coat composition D were mixed in a weight ratio of 1:1 to prepare hard coat composition E.
[0079] <Hard Coat Composition F> Hard coat composition F was prepared by mixing the above hard coat composition B and hard coat composition C in a weight ratio of 3:1.
[0080] [Preparation of anti-reflective film] <Comparative Example 1> (Formation of hard coat layer) The hard coat composition B was applied to one main surface of a 50 μm-thick polyethylene terephthalate (PET) film ("Lumirror 50U48" manufactured by Toray) to form a coating film, and the coating film was dried by heating at 80° C. for 60 seconds. A high-pressure mercury lamp was used to irradiate the film with an accumulated light amount of 300 mJ / cm 2 . 2 The coating layer was cured by irradiation with ultraviolet light of 1000 ohms to form a hard coat layer having a thickness of 3.5 μm on the PET film.
[0081] (Surface treatment of hard coat layer) While the PET film on which the hard coat layer was formed was being transported under a vacuum atmosphere of 1.0 Pa using a roll-to-roll type plasma treatment device, the surface of the hard coat layer was subjected to argon plasma treatment at a discharge power of 150 W.
[0082] (Formation of anti-reflection layer) The hard coat film after plasma treatment was introduced into a roll-to-toll sputtering deposition device, and the inside of the chamber was heated to 1×10 -4After reducing the pressure to 100 Pa, a 1.5 nm thick ITO primer layer was formed by sputtering using an MFAC power supply while the film was running, and an anti-reflection layer was formed on top of it, consisting of four layers: the first layer: a 15 nm thick Nb2O5 layer (refractive index: 2.33), the second layer: a 20.5 nm thick SiO2 layer (refractive index: 1.46), the third layer: a 89 nm thick Nb2O5 layer, and the fourth layer: a 75.5 nm thick SiO2 layer. The total thickness of this anti-reflection layer was 200 nm, and the ratio of the thickness of the Nb2O5 layer (the sum of the thicknesses of the first and third layers) to the total thickness was 52%.
[0083] To form the ITO primer layer, an ITO target containing indium oxide and tin oxide in a weight ratio of 90:10 was used as the target material, with a discharge power of 2.5 kW and a deposition pressure of 0.2 Pa. To form the Nb2O5 layer (first and third layers), an Nb target was used and argon gas and oxygen gas were introduced in a volume ratio of 90:10 so that the pressure was 0.7 Pa. To form the SiO2 layer (second and fourth layers), an Si target was used and argon gas and oxygen gas were introduced in a volume ratio of 100:30 so that the pressure was 0.7 Pa. The discharge power was adjusted so that the film thickness of each layer was the set value.
[0084] <Comparative Example 2> In forming the antireflective layer, except that the thicknesses of the first, second, third and fourth layers were changed to 14 nm, 51 nm, 26 nm and 109 nm, respectively, an ITO primer layer and an antireflective layer were formed on the hard coat layer in the same manner as in Comparative Example 1, to obtain an antireflective film. The total thickness of the antireflective layer was 200 nm, and the ratio of the thickness of the Nb2O5 layer to the total thickness was 20%.
[0085] <Comparative Example 3> In forming the antireflective layer, except that the thicknesses of the first, second, third and fourth layers were changed to 5 nm, 90 nm, 5 nm and 100 nm, respectively, an ITO primer layer and an antireflective layer were formed on the hard coat layer in the same manner as in Comparative Example 1, to obtain an antireflective film. The total thickness of the antireflective layer was 200 nm, and the ratio of the thickness of the Nb2O5 layer to the total thickness was 5%.
[0086] <Example 1> An antireflection film was obtained in the same manner as in Comparative Example 2, except that hard coat composition B was used instead of hard coat composition A in forming the hard coat layer.
[0087] <Examples 2 and 3, Comparative Example 5> Antireflection films were obtained in the same manner as in Example 1, except that the thickness of the hard coat layer was changed as shown in Table 2.
[0088] <Examples 4 to 7, Comparative Examples 6 and 7> Antireflection films were obtained in the same manner as in Example 1, except that the type of hard coat composition used to form the hard coat layer and the thickness of the hard coat layer were changed as shown in Table 2.
[0089] [evaluation] <Indentation elastic modulus of anti-reflection layer> The PET film side of the anti-reflective film was attached to a slide glass via a 50 μm thick acrylic adhesive sheet (the adhesive sheet of "Comparative Example 1" in JP 2022-116859 A) to prepare a measurement sample. The anti-reflective layer of the sample was fixed on the stage of a nanoindenter (Bruker's "TI950 TriboIndenter") with the anti-reflective layer facing up, and a load was gradually applied using a Berkovich (triangular pyramid)-shaped diamond indenter (tip curvature radius: 0.1 μm) in a measurement environment of 23 ° C. and 50% relative humidity, and the load was gradually returned to 0 after the maximum load was reached. The indentation elastic modulus Er was calculated from the slope A at a depth of about 10 nm in the unloading curve using the following formula.
[0090] Er = (S√π) / (2√A) S: Slope of the unloading curve π: Pi A: Projected contact area between the indenter and the sample The projected contact area A between the indenter and the sample was determined by the method described in JP-A-2005-195357.
[0091] <Indentation elastic modulus of hard coat layer> The anti-reflection film was embedded in embedding resin and cut in the thickness direction with an ultramicrotome to prepare a measurement sample. The cross section of the sample was fixed on the stage of a nanoindenter with the cross section facing upward, and the indenter was pressed into the cross section of the hard coat layer to perform an indentation test in the same manner as above. The indentation elastic modulus Er was calculated from the slope A of the unloading curve at a depth of about 300 nm.
[0092] <Reflectance> A spectrophotometer (Hitachi High-Technologies Corporation "U4100") was used to measure the reflection spectrum of the anti-reflection layer side of the anti-reflection film, and the reflection Y value of standard light source D65 was calculated under the conditions described in JIS Z 8722. A reflection Y value of 1.0% or less was rated as OK, and one exceeding 0.5% was rated as NG.
[0093] <Bending resistance> (Repeated bending test) The anti-reflection film was cut into a rectangle of 25 mm width x 100 mm length, with the long side in the conveying direction (MD) during roll conveyance, using a laser processing machine (GCC's "LaserPro Spirit GLS"). A bending jig was attached to the short side of the test piece using a planar body no-load U-shaped expansion and contraction tester (Yuasa System Co., Ltd.), and a repeated bending test was performed under the following conditions in a thermostatic chamber at a temperature of 23°C and a relative humidity of 50%, with the anti-reflection layer side facing inward. Bend radius: 1.5mm Bending angle: 180° Bending speed: 1 second / time Number of bends: 400,000
[0094] (Flexibility when open at low temperature) A 50μm thick acrylic adhesive sheet was attached to the PET film side of the anti-reflection film, and a rectangle with a width of 10mm and a length of 100mm, with the MD being the long side, was cut out by a laser processing machine. The adhesive layer of the test piece was attached to the test stand of a thermostatically-controlled clamshell-type bending tester (Yuasa System Devices, "Chamber-CS-m"), and the sample was kept in an open (stretched) state for 1 hour in an atmosphere at -20°C, and then opened and closed 10 times (bending and stretching were repeated 10 times) with a bending radius of 2.04mm.
[0095] (Flexibility in a closed state at low temperatures) A sample was prepared in the same manner as in the open state test described above, attached to the test stand, and held in a closed state (bent at 180°) in an atmosphere at -20°C for 1 hour, after which the sample was opened and closed 10 times.
[0096] (Evaluation of bending resistance) After each of the above tests, the samples were observed under an optical microscope to check for the presence or absence of cracks (clouding of the anti-reflection layer) in the bent portion. Those that showed no cracks in the bent portion were rated as OK, and those that showed cracks were rated as NG.
[0097] <Stress in a bent state> When the antireflection films of the examples and comparative examples were bent 1180° with the antireflection layer side facing inward at a bending radius of 2.0 mm, the compressive stress of the hard coat layer and the antireflection layer was modeled and calculated using nonlinear finite element analysis software (Marc, manufactured by MSC Software).
[0098] (Calculation model) A two-dimensional mesh was created with the length X of the sample being 100 mm and the thickness Y being the total thickness of the anti-reflection film of each Example and Comparative Example (the total of the PET film, the hard coat layer and the anti-reflection layer). The mesh sizes were set as shown in Table 1 for each of the following: Region A: X-direction coordinates 0 to 10.41796875 mm and 89.58203125 to 100 mm (regions at both ends); Region C: X-direction coordinates 10.5 to 89.5 mm (center region); Region B: X-direction coordinates 10.41796875 to 10.5 mm and 89.5 to 89.89.58203125 mm (part between Region A and Region B). The number of divisions of the mesh size in the Y direction in Table 1 indicates how many meshes are divided in the thickness direction.
[0099] [Table 1]
[0100] As shown in Figure 2, rigid models with a length of 48 mm were set on both ends, and 10 mm areas on each end of the mesh were fixed to the rigid models. The rigid model on the left side was rotated 180° so that the surface on the anti-reflection layer side was on the inside, and the mesh was bent 180° with a bending radius r = 2 mm (bending diameter D, which is the distance between the faces of the two rigid models, was 4 mm) as shown in Figure 2.
[0101] (Enter the physical properties of each layer) The material property settings for the relevant parts of the mesh were set to hypoelastic for the PET film, isotropic elastoplastic for the hard coat layer and anti-reflective layer, and the indentation modulus of each material was entered as the elastic modulus for the PET film, hard coat layer, and anti-reflective layer.
[0102] (Model calculation results) The stress in the direction perpendicular to the bending radius direction (see Fig. 3) at the bending center (X = 50 mm) was calculated, and the stress value along the thickness direction of the antireflection film was plotted. Fig. 4 is a graph showing the simulation results of the antireflection film of Comparative Example 1, in which the horizontal axis is the coordinate in the thickness direction with the outer surface (PET film surface) set to 0, and the horizontal axis is the stress plotted. A plus sign for stress indicates tensile stress, and a minus sign for stress indicates compressive stress.
[0103] The larger the coordinate in the thickness direction, the larger the compressive stress. In the hard coat layer (HC), the compressive stress was maximum at the interface on the anti-reflection layer side, and in the anti-reflection layer (AR), the compressive stress was maximum on the surface (the surface opposite to the hard coat layer). In Comparative Example 1, the compressive stress S HC is 426 MPa, and the compressive stress S at the surface of the anti-reflection layer (AR) (coordinate in the thickness direction: 53.7 μm) AR The maximum compressive stress S of the hard coat layer was 576 MPa. HC is the maximum compressive stress of the anti-reflection layer, S AR asked for.
[0104] For the anti-reflection films of Examples 1 to 7 and Comparative Examples 1 to 7, the structure of the hard coat layer (composition, thickness, and indentation elastic modulus measurement results), the structure of the anti-reflection layer (thickness, thickness ratio of the Nb2O5 layer, and indentation elastic modulus measurement results), the evaluation results of the reflectance and bending resistance of the anti-reflection film, and the compressive stress S of the hard coat layer and the anti-reflection layer when the anti-reflection film is bent are shown. HC and S AR The model calculation results are shown in Table 2. In some comparative examples, the evaluation of bending resistance was not performed, and those that were not evaluated are indicated in Table 2 as "ND."
[0105] [Table 2]
[0106] In Comparative Example 1, in which the thickness ratio of the niobium oxide layer in the antireflection layer is 52%, the elastic modulus of the antireflection layer is large at 25 GPa, and accordingly, the compressive stress S AR In Comparative Example 4, in which the composition of the hard coat layer was changed to make the elastic modulus of the hard coat layer smaller than that of Comparative Example 1, the S AR The bending resistance test was evaluated as NG in all cases.
[0107] In Example 1, in which an antireflection layer having a thickness ratio of 20% of the niobium oxide layer was formed on the same hard coat layer as in Comparative Example 4, the elastic modulus of the antireflection layer was smaller than that in Comparative Example 4, and the compressive stress S AR In Example 1, the compressive stress S of the hard coat layer was small. HC was smaller than that of Comparative Example 4. The antireflection film of Example 1 was good in all items in the bending resistance test, and showed excellent bending resistance.
[0108] The antireflection films of Examples 4 to 6, which had a hard coat layer with an even lower elastic modulus than that of Example 1, also showed excellent flex resistance, similar to Example 1. On the other hand, the antireflection film of Comparative Example 7, which had a hard coat layer with an even lower elastic modulus than that of Example 6, was inferior in repeated flex resistance. Furthermore, when the antireflection film of Comparative Example 7 was bent after being held in an open state at a low temperature, cracks occurred in the antireflection layer.
[0109] The anti-reflection film of Comparative Example 2, which had a hard coat layer with a higher elastic modulus than that of Example 1, had good repeated bending properties. However, when the film was bent after being held in an open state at a low temperature, cracks occurred in the anti-reflection layer. When the film was bent after being held in a closed state at a low temperature, cracks also occurred in the anti-reflection layer.
[0110] When comparing Comparative Example 2, Example 1, Examples 4 to 6, and Comparative Example 7, which have the same thickness of the hard coat layer and the same configuration of the antireflection layer, the compressive stress S of the hard coat layer decreases with the decrease in the elastic modulus of the hard coat layer. ARdecreases, while the compressive stress S of the anti-reflection layer HC tended to become larger.
[0111] In comparison with Comparative Examples 1 to 3 in which the material and thickness of the hard coat layer are the same, the compressive stress S of the hard coat layer decreases with the decrease in the elastic modulus of the antireflection layer. AR and the compressive stress S of the anti-reflection layer HC The antireflection film of Comparative Example 3 had a small stress when bent, but the reflectance exceeded 1%, and the antireflection properties were insufficient.
[0112] In Examples 2 and 3, the same hard coat material as in Example 1 was used, but the thickness of the hard coat layer was changed. HC and S AR The value was approximately the same as in Example 1, and the film had excellent flex resistance like Example 1. A similar tendency was observed in comparing Examples 6 and 7.
[0113] On the other hand, in Comparative Example 5, in which the same hard coat material as in Example 1 was used and the thickness of the hard coat layer was set to 14 μm, HC and S AR was significantly increased as compared to Example 1, and the bending resistance of the antireflection film was accordingly decreased. A similar tendency was observed in the comparison between Example 5 and Comparative Example 6.
[0114] In all of Examples 1 to 7, in which the antireflection film had excellent bending resistance, the compressive stress S of the hard coat layer when bent HC is 375 MPa or less, and the compressive stress S of the anti-reflection layer when bent AR On the other hand, in Comparative Examples 1, 2, and 4 to 7, S HC is greater than 375 MPa or S AR was above 530MPa.
[0115] From the above results, by adjusting the elastic modulus and thickness of the hard coat layer constituting the antireflection layer, and the elastic modulus of the antireflection layer, etc., it is possible to control the compressive stress S of the hard coat layer and the antireflection layer when the antireflection film is bent. HC and S AR It is possible to reduce S HC and S AR It can be seen that an anti-reflection film with a small value has excellent bending resistance. [Explanation of symbols]
[0116] 1 Transparent film substrate 2 Hard coat layer 5 Anti-reflection layer 50 primer layer 51,53 High refractive index layer (niobium oxide layer) 52,54 Low refractive index layer (silicon oxide layer) 100 Anti-reflective film
Claims
1. An antireflection film comprising a hard coat layer and an antireflection layer made of a plurality of thin films having different refractive indices on one main surface of a transparent film substrate, The reflectance is 1% or less, The maximum compressive stress S of the hard coat layer when the substrate is bent 180° with the anti-reflection layer side facing inward and with a bending radius of 2 mm HC is 375 MPa or less, and the maximum value of the compressive stress of the antireflection layer is 530 MPa or less; Anti-reflective film: However, the compressive stress is a calculated value based on a finite element model.
2. the antireflection layer includes at least one high refractive index layer and at least one low refractive index layer, the high refractive index layer is a thin film containing niobium oxide as a main component, The ratio of the thickness of the high refractive index layer to the total thickness of the antireflection layer is 10 to 40%. The anti-reflective film according to claim 1 .
3. The anti-reflection film according to claim 2 , wherein the low refractive index layer is a thin film containing silicon oxide as a main component.
4. The antireflection film according to claim 2 , wherein the antireflection layer includes two or more of the low refractive index layers and two or more of the high refractive index layers.
5. 4. The antireflection film according to claim 1, wherein the antireflection layer has an indentation elastic modulus of 20 to 24 GPa.
6. The optical laminate according to any one of claims 1 to 3, wherein the antireflection layer has an inorganic primer layer on a surface in contact with the hard coat layer.
7. 4. The anti-reflection film according to claim 1, wherein the hard coat layer has a thickness of 1 to 10 μm and an indentation modulus of elasticity of 6.5 to 11 GPa.
8. An image display device, comprising an anti-reflection film according to any one of claims 1 to 3 disposed on a viewing side surface of an image display medium.
Citation Information
Patent Citations
Antireflection film and polarizing plate using the same
JP2009047876A